Pengaruh Customer Experience Dan Customer Satisfaction Terhadap Pembelian Ulang Produk Hanasui Mattedorable Lip Cream (Boba Edition) - Nahdila Trisna Dwi Saryono; Ety Dwi Susanti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this research is to determine the influence of Customer Experience, Customer Satisfaction, and the influence of Customer Experience and Customer Satisfaction simultaneously on repeat purchases of Hanasui Mattedorable Lip Cream (Boba Edition) products. The method used in this research is explanatory research with a quantitative approach. With the results, Customer Experience partially has a positive and significant effect on repeat purchases of Hanasui Mattedorable Lip Cream (Boba Edition) products, Customer Satisfaction partially has a positive and significant effect on Repurchases of Hanasui Mattedorable Lip Cream (Boba Edition) products, and Customer Experience, and Customer Satisfaction simultaneously influence repeat purchases of Hanasui Mattedorable Lip Cream (Boba Edition) products.